Twenty-five Years of Securitization Theory: A Corpus-based Review. (May 2023) - Baele, Stephane J; Jalea, Diana
Twenty-five years after its initial formulation, securitization theory is at a crossroads: attempts to critically scrutinize its achievements and shortcomings proliferate, concerns about the theory's eurocentrism are articulated, and a heated row shakes the field following accusations of racism. In this unstable context, the present article systematically reviews a corpus of 171 securitization papers published in 15 major International Relations journals since 1995, identifying two major imbalances characterizing securitization theory research. First, rich theoretical development has not been matched by sustained efforts to strengthen empirical work; second, the theory has not been globally embraced, displaying instead a narrow, distinctly local anchoring. By shedding light on these two issues and their relationships, this review article aims to provide clear and actionable observations around which scholars could productively re-organize the ongoing debates and controversies.